Dinamika Implementasi Kebijakan Bantuan Langsung Tunai (BLT) Studi Kasus di Kaupaten Kebumen - Wahyu Siswanti (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2008)
Bnatuan Langsung Tunai (Cash Transfer Subsidy) was targeted to the poor for compensating the fuel price hike in 2005. In Kebumen Regency, there was difference of perception or understanding and interest policy actors in the implementation of Cash Transfer Subsidy. The difference was not only caused by limited time in preparing program affecting absence of perception similarity, but also conflict of interest in various bureaucratic layers and target groups.The difference of perception and interest policy actors finally resulted in conflict between actors, deviation of Cash Transfer Subsidy practice, both from process of early program recordings to phase of fund distributions and mistargeting. Other implications were appearances of moral hazard. Those who were actually better off have claimed themselves to be poor and apply for the subsidy fund. Solution of even distribution done by actors of lowest level indicated that there was weak perception for policy goal and effort to reduce social conflict.The government needs to better prepare before the programme is launched. Socialization, coordination among institutions can avoid misperception or misunderstanding of policy actors. In addition, it is necessary for the regency government to have commitment and to involve local community to minimize problems in the implementation.